Isolation and morphological identification of soil fungi from agricultural soil in Kuantan - Ahmad Azmi, Nur Sabrina; Hisham, Asma Adiba (Zibeline International Publishing, 2021)
Soil fungi possess a great number of potential benefits that could be applied in various fields. They are well-known for acting as plant-growth promoter, biocontrol agent of plant diseases and involves in bioremediation. In this study, the fungi were isolated from used agricultural soil in Glasshouse and Nursery Complex (GNC), International Islamic University Malaysia, Kuantan, Pahang using serial dilution and plating techniques. Around 10 isolates of soil fungi were successfully isolated and the identification of all isolates were based on their cultural and morphological characteristics. The fungi were discovered to be from genus Cladorrhinum, Penicillium, Paecilomyces and Aspergillus.